2018
DOI: 10.3892/ol.2018.8347
|View full text |Cite
|
Sign up to set email alerts
|

An indel polymorphism in the 3' untranslated region of JAK1 confers risk for hepatocellular carcinoma possibly by regulating JAK1 transcriptional activity in a Chinese population

Abstract: The purpose of the present study was to assess whether the rs112395617 polymorphism located in the Janus kinase 1 () 3' untranslated region (3' UTR) was associated with the risk of hepatocellular carcinoma (HCC), and to explore the potential mechanism of action. Genomic DNA was extracted from peripheral blood of 290 patients with HCC and 320 controls. A polymerase chain reaction-polyacrylamide gel electrophoresis assay was used to genotype the rs112395617 polymorphism. Quantitative (q)PCR was used to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Our previous study compared expressions of miRs in NEC, spontaneous intestinal perforation, and surg‐ctl bowel tissues and demonstrated significant up‐regulation of miR‐431 in NEC (7.05‐fold) and spontaneous intestinal perforation (4.15‐fold), suggesting possible involvement of miR‐413 in gut inflammation of these neonatal conditions (9). To date, very little has been reported on miR‐431 besides its involvement in the development of muscle (21, 22), neuronal conditions (23, 24), and pancreatic and hepatic malignancy (25, 26). Any potential influence of miR‐431 on adult gut inflammatory conditions such as Crohn's disease and ulcerative colitis has also not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study compared expressions of miRs in NEC, spontaneous intestinal perforation, and surg‐ctl bowel tissues and demonstrated significant up‐regulation of miR‐431 in NEC (7.05‐fold) and spontaneous intestinal perforation (4.15‐fold), suggesting possible involvement of miR‐413 in gut inflammation of these neonatal conditions (9). To date, very little has been reported on miR‐431 besides its involvement in the development of muscle (21, 22), neuronal conditions (23, 24), and pancreatic and hepatic malignancy (25, 26). Any potential influence of miR‐431 on adult gut inflammatory conditions such as Crohn's disease and ulcerative colitis has also not been described.…”
Section: Discussionmentioning
confidence: 99%
“…201 However, our laboratory has shown that while expression. 203 While intriguing, more precise functional dissection of these polymorphisms and their interplay with microRNAs is required for full understanding of their effect on antiviral immunity.…”
Section: Hos T G Ene Ti C Variati On In the Rna Reg Ul Ati On Of The Antivir Al Re Sp Onsementioning
confidence: 99%
“…Of these isoforms, only p42 or p46 are expressed robustly at the protein level due to the instability of the other protein variants and of the RNA isoforms encoding them. [203][204][205] The expression of OAS1 p42 or p46 is controlled by the SNP rs10774671A/G in the splice acceptor site of exon 6. The G allele of this SNP shifts the splice acceptor site by one nucleotide and thus generates p46 with a novel C-terminal amino acid sequence that includes a terminal CaaX motif, subject to post-translational prenylation.…”
Section: Hos T G Ene Ti C Variati On In the Rna Reg Ul Ati On Of The Antivir Al Re Sp Onsementioning
confidence: 99%
“…Somatic 3'UTR variants are more common in solid tumours compared to normal cells. However, it has been reported that variations defined in the 3'UTR regions of genes involved in the carcinogenesis process may be associated with low survival and poor prognosis [12].…”
Section: Introductionmentioning
confidence: 99%